A study on tax compliance in tax amnesty policy - Bambang Juanda; Lukytawati Anggraeni; Putri Mahestyanti; Benny Robby Kurniawan (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2022)
The Indonesian Government implemented the tax amnesty policy in 2016 with several objectives, among others, to achieve tax revenue targets in the short-term, while in the long term it is to improve tax compliance, especially for the wealthier Indonesian citizens, while also accelerating tax reforms to increase tax participation’s rate. This paper examines the effects of factors (wealth, tariff period system, tax fines, audit probability, and taxpayers’ expectation of future tax amnesty) on tax compliance. Tax compliance is measured by the percentage of assets unit, the percentage of assets value reported by taxpayers, and the taxpayer participation rate in tax amnesty policy. This behavioral economics study uses an experimental approach because it is impossible to use conventional methods. The result showed that the taxpayers with higher wealth have lower compliance and prefer to participate in tax amnesty programs at the lowest tariff rate. The government's effort to impose fines and audits shows a greater effect on tax compliance. The tax amnesty policy should only be implemented once because if people expect a similar policy to be applied in the future, they will wait for the policy so that tax compliance is low. A tax amnesty policy—while it can increase tax revenues in the short term—could reduce tax compliance, especially if the government imposes a second tax amnesty in the future.